A STUDY OF THE WOMEN’S RIGHT TO WORK - Priyanka Rubi (International Journal of Multidisciplinary Research and Studies, 2021)
After more than thirty years of work, the United Nations Commission on the Status of Women (CSW) finally finished drafting "The Convention on the Elimination of All Forms of Discrimination against Women" (CEDAW). This was done in response to the increasing number of atrocities and instances of discrimination that were committed against women. The Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) was approved by the United Nations General Assembly (UNGA) on the 18th of December 1979; however, it did not become an official international treaty until the 3rd of September 1981. As of this moment, about 189 nations have ratified CEDAW, and 165 nations have ratified CEDAW-OP (Optional Protocol). The work done by the CSW has been critical in bringing to light all of the domains in which women have been denied equality with men. This is an important goal of the organization. Them attempts to advance the status of women have led to the creation of a number of declarations and conventions, the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) being the most important and all-encompassing of these. The text of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) was drafted by working groups of the CSW in 1976, and a working group of the Third Committee of the General Assembly carried out lengthy deliberations between 1977 and 1979. The execution of the recommendations made during the World Conference of the International Women’s Year, which took place in Mexico City in 1975, by the World Action Plan was another factor that contributed to the encouragement of the creation of the CEDAW statement. As a result, the United Nations General Assembly passed resolution 34/180, which led to the adoption of the CEDAW text in order to codify thoroughly international legal norms for women.